Compliance of Nurses in the Use of Personal Protective Equipment (PPE) During the COVID-19 Pandemic in a Private Hospital in Western Indonesia - Ballsy Cicilia Albertina Pangkey; Bella Kezia Elisabeth Purba; Winestin Daeli; Elice Zalukhu; Masrida A. Panjaitan (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2023)
Background: Corona Virus Disease (COVID-19) is a respiratory disease caused by SARS-CoV-2, which spreads through droplets, aerosols, and contact with the eyes, nose, or mouth with hands contaminated by the virus. One preventive measure is the use of personal protective equipment (PPE). Nurse compliance in using PPE can have positive impacts on nurses. The research objective is to assess the overview of nurse compliance in the use of PPE during the COVID-19 pandemic. Objectives: This research aims to determine nurse compliance with the use of Personal Protective Equipment (PPE) during the COVID-19 pandemic. Methods: The research method employs a quantitative approach with an analytical descriptive research design. A Purposive sampling technique was used to select 49 nurses as the research sample. The instrument used was a questionnaire, and univariate data analysis was conducted. The study was conducted from March 30 to April 13, 2022. Results: The findings of this research indicate that the level of nurse compliance in using PPE during the COVID-19 pandemic falls into the compliant category, with all 49 nurses (100%) exhibiting compliance. Conclusion: Nurses demonstrate compliance in using PPE during the COVID-19 pandemic.